PENGARUH BAURAN PEMASARAN JASA TERHADAP PROSES PENGAMBILAN KEPUTUSAN DAN KEPUASAN DEBITUR PADA PT. PERMODALAN EKONOMI RAKYAT PROVINSI RIAU - Norman Rachman '; Samsir ' '; Liswar hamid ' (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2014)
This study aimed to analyze the effect of marketing mix toward decisions making process and satisfaction debtor on Capital of Economy the People's of Riau Province. The instrument used for data collection was a questionnaire. The study population was all employees of PT Riau Provincial People's Economic Capital totaling 774 people. The sample in this study is based on the use of Taro Yamane formula obtained by 90 people. Analysis using multiple linear regression analysis. The calculations show that There is no significant effect between the positive and the product purchase decision, there is a significant and negative influence on purchasing decisions between cost, there is no significant effect between the positive and the location of the purchase decision, there is no significant effect between the negative and promotion on purchase decisions, there is no significant effect between the positive and the purchase decision, there is no significant effect between the positive and the physical facilities of the purchase decision, there is a significant and positive effect of the process on purchasing decisions, there is no significant influence and positive among the products to customer satisfaction, there is no significant effect between the negative and the cost of consumer satisfaction, there is no significant effect and positive relationship between the location of consumer satisfaction, there is no significant effect between the negative and the promotion of consumer satisfaction, a significant difference between the positive and the customer satisfaction, there is no significant effect between the negative and the physical means to customer satisfaction, there is a significant and positive effect between customer satisfaction and process towards a significant difference between the positive and to the satisfaction of the consumer purchase decision on PT. People in the Economic capital of Riau province .Kata Kunci : Marketing Mix, Purchase Decision, Customer Satisfaction PENDAHULUAN Pemasaran